Sacrificial Bioprinting of a Mammary Ductal Carcinoma Model. Issue 10 (27th May 2019) - Duchamp, Margaux; Liu, Tingting; van Genderen, Anne M.; Kappings, Vanessa; Oklu, Rahmi; Ellisen, Leif W.; Zhang, Yu Shrike
Abstract : Cancer tissue engineering has remained challenging due to the limitations of the conventional biofabrication techniques to model the complex tumor microenvironment. Here, the utilization of a sacrificial bioprinting strategy is reported to generate the biomimetic mammary duct‐like structure within a hydrogel matrix, which is further populated with breast cancer cells, to model the genesis of ductal carcinoma and its subsequent outward invasion. This bioprinted mammary ductal carcinoma model provides a proof‐of‐concept demonstration of the value of using the sacrificial bioprinting technique for engineering biologically relevant cancer models, which may be possibly extended to other cancer types where duct‐like structures are involved. Abstract : The generation of a biomimetic mammary duct‐like structure within a hydrogel matrix through the use of sacrificial bioprinting is reported. When populated with breast cancer cells, genesis of ductal carcinoma and its subsequent progression could be modeled. This bioprinted mammary ductal carcinoma model provides a proof‐of‐concept demonstration of the value of using the bioprinting technique for engineering biologically relevant cancer models.